A novel circular RNA, hsa_circ_0043278, acts as a potential biomarker and promotes non-small cell lung cancer cell proliferation and migration by regulating miR-520f. Issue 1 (4th December 2019) - Cui, Jinggang; Li, Wei; Liu, Guohua; Chen, Xiaojun; Gao, Xiaolai; Lu, Huiling; Lin, Dang
Abstract: More and more circular RNAs (circRNAs) revealed to play a critical role in the initiation and progression of cancer, however, the effects of circRNAs on non-small cell lung cancer (NSCLC) remain largely undetermined. In the present study, we screened the dysregulated circRNAs in paired NSCLC and normal samples from GEO database and identified circ_0043278 was to be significantly up-regulated in NSCLC and demonstrated it promotes NSCLC progression in vitro and in vivo . Then, we revealed the expression of miR-520f, a downstream factor of circ_0043278, was significantly down-regulated in NSCLC and acted as a tumor inhibitor. In addition, we revealed that circ_0043278 sponged miR-520f, which was demonstrated to target ROCK1, CDKN1B, and AKT3 in NSCLC cells. In conclusion, circ_0043278 promoted NSCLC cell proliferation, invasion, and migration by increasing ROCK1, CDKN1B, and AKT3 expressions through direct inhibition of miR-520f.